Impact of Endoplasmic Reticulum Stress Sensors on Pectolinarin Induced Apoptosis - Song, Ji-Hye; Kwon, Kisang; Kwon, O-Yu; Lee, Eun-Ryeong; Kim, Seung-Whan; Kang, Kyung-Hee (Frontiers in Public Health, 2020)
Pectolinarin, [5,7-Dihydroxy 4′,6-dimethoxyflavone 7-rutinoside, 7-[[6-O-(6-Deoxy-α-L-mannopyranosyl)-β-D-glucopyranosyl] oxy]-5-hydroxy-6-methoxy-2-(4-ethoxyphenyl)-4H-1-benzopyran-4-one], has been stated one of the major compounds in Cirsium nipponicum (Maxim.) Makino. It is characterized by biological functions of hepatoprotective, anti-inflammatory and antiobesity activities. In this research, it was explained that pectolinarin causes apoptosis in PC12 cells conducted by DNA fragmentation and formation on apoptotic bodies through the activation of ER stress sensors (ATF6 fragmentation and eIF2α phosphorylation). The result of treating the PC12 cells with 50 μM pectolinarin for 24 h has come to increase ATF6 mRNA expression up to 1.6 times, PERK expression up to 1.7 times and IRE1 expression up to 1.4 times, respectively, compared to those of the control. ATF6 fragmentation by pectolinarin treatment was increased about 2 times compared with its control, and phosphorylation of eIF2α was increased 2.5 times. The results proposed that the perception of the molecular mechanisms underlying pectolinarin-caused apoptosis may be useful in new natural medicinal products and health supplements for the apoptosis-related diseases.